Posterior Shoulder Instability in Tennis Players: Aetiology, Classification, Assessment and Management - Lyn Watson; Gregory Hoy; Timothy Wood; Tania Pizzari; Simon Balster; Shane Barwood; Sarah Ann Warby (North American Sports Medicine Institute, 2023)
# Background Micro-traumatic posterior shoulder instability (PSI) is an often missed and misdiagnosed pathology presenting in tennis players. The aetiology of micro-traumatic PSI in tennis players is multifactorial, including congenital factors, loss of strength and motor control, and sport-specific repetitive microtrauma. Repetitive forces placed on the dominant shoulder, particularly combinations of flexion, horizontal adduction, and internal rotation contribute to the microtrauma. These positions are characteristic for kick serves, backhand volleys, and the follow-through phase of forehands and serves. The aim of this clinical commentary is to present an overview of the aetiology, classification, clinical presentation, and treatment of micro-traumatic PSI, with a particular focus on tennis players. # Level of Evidence 5